(untitled) (Web of Teachers: Inderscience Research, 2025)
The article examines the impact of globalization processes on the traditionalist tendencies of Russian and Uzbek prose, with an emphasis on the rethinking of gender identity in the literary text. The author analyzes how global cultural and social transformations affect literary images, redefine gender roles and modify the system of national and cultural coordinates. Particular attention is paid to how traditionalism, which retains the functions of cultural continuity, enters into a dialogue with the challenges of the modern era without losing its semantic depth. A comparative analysis of Russian and Uzbek prose reveals similar strategies for responding to global challenges, including through the modification of the literary language, the complication of the character structure and the introduction of new narrative models. Gender representation in the context of globalization acquires a new dimension, in which the national and the universal begin to coexist, interacting as equal discursive principles. These observations contribute to a deeper understanding of how literature preserves identity in the face of expanding cultural boundaries.